Bloch Points Stabilization by Means of Diameter Modulations in Cylindrical Nanowires - Escrig-Murua, J (Elsevier B.V., 2022)
The storage of information in long nanowires with a succession of independently oriented magnetic segments is of great practical use. It requires both the possibility of independently orienting the magnetization of each segment and great stability of the inscribed magnetization regarding spontaneous reversals. A practical way to separate sectors along the wire is by short modulations wider than the original wire that acts as a valve separating segments with independent magnetic orientations. When these two orientations are different, a Bloch Point (BP) develops within the modulation. It is precisely this BP that controls the stability of the system. In the present paper, we study the robustness of such BPs depending on geometrical parameters, such as the diameter and thickness of the cylindrical modulations as well as on external magnetic fields applied along the axis. © 2022 The Authors